Therapeutic use of Cannabidiol in dogs: A narrative review (Research, Society and Development, 2024)
Cannabidiol (CBD) is a non-psychotropic phytocannabinoid extract from Cannabis sativa. CBD is increasingly being explored as an alternative to conventional treatments for a e therapeutic role. Several studies support the benefits of CBD such as controlling seizures, acute and chronic pain and decreased pruritus. Other preliminary efficacies point to its role in the inflammatory, immunomodulatory, antiproliferative and associated cell death response. This work aims to carry out a recent and updated bibliographical analysis with reliable scientific evidence related to the mechanisms of action of CBD, including pharmacokinetics, safety, regulation and efficacy in improving pathology in dogs.